Digitales Kulturerbe : Bewahrung und Zugänglichkeit in der wissenschaftlichen Praxis - Robertson-von Trotha, Caroline Y. [Hrsg.]Schneider, Ralf H.[Hrsg.] (Kulturelle Überlieferung - Digital, 2015)
Today, access to our cultural heritage is mostly of a digital nature. Cultural assets that are not directly accessible via the Internet are at risk of becoming irrelevant. It is up to us, as contemporary witnesses to this change, to help shape the digital future of our cultural heritage in a responsible manner. This book provides insights into measures to preserve that heritage and make it accessible, and discusses the accompanying opportunities, challenges, and dangers.